Near-infrared imaging in re-operative parathyroid surgery: first description of autofluorescence from cryopreserved parathyroid glands - Moore, Edwina C. (Gland Surg, 2019)
Identification of parathyroid glands is one of the primary tenets in endocrine surgery. Multiple localizing techniques have been described and are in use in routine practice. More recently near-infra red imaging has been gaining popularity and is used for identification in real time. Parathyroid glands are unique in that they fluoresce when excited by near-infrared light, without the use of a biomarker. This is called autofluorescence (AF). In this case report we describe the presence of persistent AF by thawed parathyroid glands which have previously been cryopreserved. We confirm that the mechanism behind AF involves an intrinsic primary fluorophore, unique to parathyroid glands.